PARADIGMA AKUNTANSI SYARIAH - Rahmat Ilyas (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
Sharia transactions are based on the paradigm that the universe is entrusted by God as a mandate (divine trust) and a means of happiness for all mankind. Accounting is a very static event. Accounting always develops following the evolutionary pattern of society. This development of accounting is very significant, as it has happened that accounting has developed from the unification of religious aspects towards efforts to separate religions in economic matters. Sharia accounting is based on please help, this causes various differences with conventional accounting based on the capitalist system. The Islamic accounting paradigm considers various paradigms by showing differences in accounting ideology. Based on this religious foundation, there are three interconnected dimensions, namely: 1) seeking the pleasure of Allah as the main objective in determining socio-economic justice; 2) realizing benefits for society, namely by fulfilling obligations to society, and 3) pursuing personal interests.